Effect of layer thickness ratio on microstructure and mechanical properties of TiC–WC/TiC–TiN laminated ceramics - ZHENG Xifan; JIANG Longkai; GAO Jiaojiao; SONG Jinpeng; MENG Weiqi; WANG Yao (Fenmo yejin jishu)
The TiC–WC/TiC–TiN laminated ceramics with the layer thickness ratios as 2:1, 1:1, 1:2, 1:3 and 1:4, respectively, were prepared by dry pressing and vacuum hot pressing sintering with TiC as the base materials and WC and TiN as the additive phases of the TiC–WC (TW) layer and TiC–TiN (TT) layer, respectively. The effects of layer thickness ratio on the residual stress, microstructure, and mechanical properties were investigated. The results show that the residual compressive stress existing in the TW layer gradually increases with the increase of TT layer thickness, and the residual tensile stress existing in the TT layer gradually decreases, but the difference between the two is relatively stable. With the increase of the TT layer thickness, both the hardness of the TW layer and the relative density of the laminated ceramics increase slowly, while the fracture toughness of the TW layer and the flexural strength of the laminated ceramics increase first and then decrease. The hardness of the TT layer slightly decreases with the increase of the TT layer thickness, while the fracture toughness keeps decreasing. When the layer thickness ratio is 1:3, the microstructure defects of the laminated ceramics are fewer, the grain size is uniform, the combination is tight, and the best mechanical properties are obtained as the relative density of (96.47±0.02)% and the flexural strength of (946.01±19.1) MPa. At this time, the hardness and fracture toughness of the TW layer are (16.68±0.17) GPa and (10.19±0.22) MPa·m1/2, respectively, and the hardness and fracture toughness of the TT layer are (15.73±0.15) GPa and (7.78±0.26) MPa·m1/2, respectively. Meanwhile, it is observed that the average grain size of the TT layer is significantly smaller than that of the TW layer. Crack deflection and crack bridging occur when the cracks cross the junctions of the layers, and the fracture modes are transgranular fracture and intergranular fracture.